Dynamic Response of Cement–Fly Ash Mixed Pile Composite Foundation Under Wave Load - Zhang, Haojin; Zhou, Shengquan; Wang, Rui; Li, Dongwei (Frontiers in Earth Science, 2022)
CFMP（Cement and fly ash mixing piles）are used to reinforce fly ash foundation to solve the problem of a large amount of fly ash accumulation in coastal areas. CFMP fly ash composite foundation is used as the foundation of coastal and coastal engineering. Through indoor model test, the bearing characteristics and load transfer mechanism of CFMP fly ash composite foundation under wave load were investigated. The results show that: The results show that with the increase of wave load, the horizontal resistance of fly ash stratum increases gradually, the zero point of soil resistance moves down, and the m value shows nonlinear characteristics. The pile bending moment, pile displacement and horizontal resistance of CFMP composite foundation are concentrated in the upper pile and fly ash stratum, which can improve the ability of composite foundation to resist horizontal load by improving the physical and mechanical properties of the upper fly ash stratum. Through the calculation of load displacement curve, it is found that the measured displacement value is closer to the p-y curve method. Accompany with the increase of number of cycle loading hysteresis loop moves to the right and accumulated from the elastic and plastic deformation of pile show that fly ash behavior gradually shift to the elastic stage, cyclic loading can reduce the horizontal deformation modulus of composite foundation CFMP caused pile - fly ash system of weakening, in peak load reaches level under critical state displacement curve showed a trend of rapid growth of nonlinear, cyclic cumulative failure occurs and the cyclic load limit state is reached, which affects the service performance of the whole structure.